Musical Instrument ‘Talempong Minangkabau’ in Organological Study - Syeilendra, Syeilendra; Parmadi, Bambang (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2022)
This study aims to photograph the traditional process of making Minangkabau talempong from start to finish. Descriptive analysis methods are used in this qualitative study. The process of making is systematical, factual, accurate, and originally analyzed by thought in the light of library reviews, and journals. In the process of making it, black clay is mixed with chaff and milled red clay. The principal ingridients were brass or copper (Cu), tin (Sn), and iron (Fe). The process begins with the production of a wax talempong model, binding the wax talempong with a clay mixture to make a cast of talempong ground, and casting off its then casting, the matter is burned to extract the wax and is in a row sent out by interlaced. Eventually, the prints were destroyed and talempong produced. After cleaning, leveling, grinding, milling, and polished, talempong is ready. There are three varieties of talempong in size: (1) large; (2) moderate; and (3) small. The talempong is traditionally displayed by striking the outside to match the tone or striking the outside to match the tone.